Harga Diri Bandar Judi Dadu di Desa Pauh 1 Rawas Ilir Kabupaten Musi Rawas Utara - Arin Deska Mapila; Zaharuddin Zaharuddin; Fajar Tri Utami (Indonesian Journal of Behavioral Studies, 2021)
This study discusses the self-esteem of dice bookies in the village of Pauh 1 Rawas Ilir, Musi Rawas Utara District. The method in this research is to use qualitative research with a descriptive approach. Furthermore, the data collection method in this study is to use observation, interviews and documentation. The results of this study indicate that the background for the three subjects to become dice bookies is due to economic factors, where the three subjects have difficulty finding other jobs while many needs must be met. Accompanied by the public's view of the work of the three subjects as dice bookies, it can be concluded that the three subjects know that the public often insults or gossips themselves but the three subjects choose to be silent and don't care.